Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/min12050528
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Kinetics of Imidacloprid, Acetamiprid and Methomyl Pesticides in Aqueous Solution onto Eucalyptus Woodchip Derived Biochar

Abstract: This work reports the application of a biochar (BC) derived from eucalyptus wood chips to remove pesticides (imidacloprid, acetamiprid and methomyl) from water. The pseudo-second order kinetic adsorption model is the best fit describing the adsorption of pesticides on BC. Furthermore, the Langmuir model correlated well with the adsorption isotherm data for acetamiprid and methomyl, while the Freundlich model was selected to explain the adsorption of imidacloprid on BC. The maximum adsorption capacities for met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 86 publications
1
18
0
Order By: Relevance
“…Their thermal stability was analyzed through thermogravimetric analysis (TGA) using a Hitachi (STA-7200) instrument. The Brunauer-Emmitt-Teller (BET) measurements were performed to determine the specific surface area and pore volume on AutoSorb (6-Quantachrome, Boynton Beach, FL, USA) [10,19]. The adsorption temperature was controlled using an Alpha Immersion thermostat (230 V, 50/60 Hz, Germany) and the initial pH was measured using a portable PHYWE pH meter (Cobra, Bremen, Germany).…”
Section: Characterization Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Their thermal stability was analyzed through thermogravimetric analysis (TGA) using a Hitachi (STA-7200) instrument. The Brunauer-Emmitt-Teller (BET) measurements were performed to determine the specific surface area and pore volume on AutoSorb (6-Quantachrome, Boynton Beach, FL, USA) [10,19]. The adsorption temperature was controlled using an Alpha Immersion thermostat (230 V, 50/60 Hz, Germany) and the initial pH was measured using a portable PHYWE pH meter (Cobra, Bremen, Germany).…”
Section: Characterization Methodsmentioning
confidence: 99%
“…The polymerization procedure was carried out in a stirred, cooled (5 • C) reactor. The APS solution was added dropwise to the monomer solution and the reaction took 24 h (Scheme 1) [10,19]. The reactor contents were then vacuum filtered and washed repeatedly with 1 M HCl, C 2 H 5 OH, and H 2 O to eliminate excess oxidant with oligomers until the filtered solution became clear.…”
Section: Pani:ppy@sio 2 Hybrid Adsorbent Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…Adsorption kinetic modelling was used to explain dye transfer from solution phase to the solid phase (Huang et al 2022, Srikhaow et al 2022, with the observed data fitted to pseudo-first-order and pseudo-second-order kinetic models. To determine the mechanism of retention of dyes on the surface of nM-SJFSB and to understand the speed control step, kinetic data were equipped with these kinetic models.…”
Section: Kinetic Modelsmentioning
confidence: 99%